COMMUNICATION NETWORK ANALYSIS OF THE ANTI-RACISM TOWARDS ASIAN CAMPAIGN ON TWITTER - Wiguna, Artha; Nugroho, Widio; Tuasikal, Rio (ASPIRATION Journal, 2022)
This study aims to determine the distribution of communication networks of the #StopAsianHate campaign on Twitter. Using the theory of Computer-Mediated Communication, this paper seeks to identify the campaign's networks in system level and actor level. To achieve this, we used a quantitative approach of Communication Network Analysis with the Netlytic and Gephi models, as well as the content analysis method. From the analysis, we found 5 independent clusters in the network. On the level system, we found that information exchange requires only 2 actors to be passed, actors retweet or like more than talk, most conversations happened one-sidedly, network dominated by few actors, and network has a clear division between the clusters represented. On the actor level, we identified two accounts that played a dominating role in the campaign, that actors have a close relationship with other actors, no influence in linking the distribution of information related, and found 6 top actors with central role. Meanwhile, from the content analysis we found that the focus of the actor's communication campaign is the sharing of opinions, information, and images.